Religion and suicide among Chinese Rural Youths - Zhang, Jie (Mental health, religion & culture, 2022)
Using data collected with psychological autopsy method, we compared 392 suicides with 416 living controls among adolescents and young adults in rural China. Informants were asked whether the subjects believed in a religion (and which religion) and whether they believed in a life after death. About 7.8% of the suicides believed in a religion compared to 5.8% of the controls. About 11.2% of the suicides believed in a life after death compared to 8.4% of the controls. Suicide was predicted by the presence of a mental illness, a history of suicide in the family, poor social support, low status (power) in the family, and less education. Belief in a life after death did not contribute to the prediction of suicide in men or in women, but belief in a religion did predict suicide for the men. Suggestions were made for future research.